IMPACT OF MOTHERHOOD ON THE CAREER OF WOMEN IN CROATIA - Sujeet Kumar Bharati (International Journal of Multidisciplinary Research and Studies, 2021)
In the 20th century, there was a significant increase in the number of women actively participating in the labour force, which resulted in one of the most revolutionary economic and social transformations of the century. This transformation was brought about as a direct result of the rise in the wage gap between men and women. In more industrialized nations, males have progressively taken on the traditional position of earner, while women have increasingly taken on the role of caretaker of the family. This growth in the number of women who are participating in the labour force has been accompanied by an increase in the average level of education and credentials held by working women. For example, according to some recent figures for the European Union, in 2016, over 44% of women (aged 30-34) had a postsecondary degree or above, whilst only 34% of males possessed that level of education. This difference in educational attainment was seen throughout all age groups (European Commission, 2017). The employment rates of women in the European Union are still lower than those of men; in 2016, the employment rate of women in the EU who were 20-64 years old was 65.3%, while the employment rate for men in the same age group was 76.8%. This disparity in employment rates is expected to continue for some time.